CONCOMITANT ROTATOR CUFF TEAR AND BRACHIAL-PLEXUS INJURY IN ASSOCIATION WITH ANTERIOR SHOULDER DISLOCATION - UNHAPPY TRIAD OF THE SHOULDER - (:unkn) unknown (LIPPINCOTT-RAVEN PUBL, 1994)
High incidences of nerve lesions or rotator cuff tears in association with shoulder dislocations have been reported. However, the simultaneous occurrence of these three lesions has only been reported once previously. This case is an example of a not so uncommon injury, which emphasizes the importance of looking for associated brachial plexus and rotator cuff lesions when examining a patient with shoulder dislocation.
Keywords: ROTATOR CUFF INJURY; BRACHIAL PLEXUS INJURY; SHOULDER DISLOCATION